Pengembangan Dan Pengujian Black Box Testing Menggunakan Teknik Equivalance Partitions Pada Aplikasi Pengarsipan Surat Di Polrestabes Palembang - Nurul Huda; Jemakmun; Kms. Muhammad Naufal (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Activities that provide activity records and documentation of existing activities in state institutions and companies will result in correspondence management activities that are archived into documents. Archives play a crucial role in state institutions and companies because they are a source of news. The purpose of archiving is an archive that is combined into a source of information that requires fast time to deliver the required information. The purpose of developing this letter archiving application is to provide web-based mail archiving which consists of the process of managing incoming and outgoing mail and making more efficient and effective mail management reports. Extreme Programming is the technique used. The research results are presented in a web-based application that makes it easier to archive and search for information sources that are more effective, efficient, and up-to-date than the previous system. It also features archive recording and correspondence filing notifications for information retrieval and correspondence reporting.